Improved energy performance of a PEM fuel cell by introducing discontinuous S-shaped and crescent ribs into flowing channels. (1st May 2021) - Dong, Pengcheng; Xie, Gongnan; Ni, Meng
Abstract: Better mass transfer, more uniform temperature distribution, small pressure drop, and improved electrochemical performance can be achieved by designing better flow field in PEM fuel cells. In this paper, based on the concept of a sinusoidal rib, two kinds of discontinuous ribs: S- shaped rib and crescent rib, are proposed and introduced into the flow channels of a PEM fuel cell. Results show that the proposed ribs improve the flow field, and the local convection effect becomes stronger due to the velocity field changes. Moreover, a better distribution of O2 concentration is obtained from the better flow pattern, resulting in an improvement of the electrochemical rate and an increase of the temperature. The pressure drop is effectively reduced, and the electrochemical efficiency is improved by up to 23.61% in the condition of high current density, compared to those of the baseline sinusoidal ribbed flow field. Highlights: The discontinuous S-shaped and the crescent ribs are introduced for a PEMFC flowing channel. Mass transfer, flow and energy performance of the PEMFC are modeled and evaluated. The enhancement of mass transport is much better than that of sinusoidal ribbed flow field. The proposed ribs improve the energy efficiency by up to 23.61% compared to a sinusoidal rib.